Respostas sintomáticas e acontecimento de corpo: direção do tratamento na clínica com idosos - Angela Maria de Sousa Mucida (2012)
The research stemmed from a finding of clinical work with the elderly, where one observes an intense relationship with the body: seen, touched, medicated talked about, described in its functionality with symptoms related in particular to the functions of the digestive tract, bowel, with the prevalence of oral and anal drive. From this clinical fact, there are three main prominent issues: the function of these symptomatic responses, how to treat them and the status of the body at an advanced age. The various articulated notions of symptoms especially by Freud and Lacan, led us to hypothesize that in all symptomatic responses, remains a key symptom, fixed, or pertaining to the primal repression, or with Lacan, the effect of fixing the primordial signifier establishment of letter of delight or designed as an event of the body; effect of lalangue. Real out of sense, and non-structural and disaffected with the passage of time. We can infer that there are no symptoms of the elderly, despite the old age. From the notions of the body, especially the theories on the Real unconscious and the, happening of the body we extract the hypothesis of the presence of an effective primary body that never ages, despite the aging body. These thesis open another way to listen to this body and the symptoms in old age beyond the idea of bodily weakness and diseases of aging. Old age is not homogenized, despite its inclusion in the social field and its categories. Indeed, psychoanalysis does not listen to the elderly, but subjects or speaking beings marked by what does not age, allied with the Real unconscious and manifest of the body. In treating, what matters is the unique way each one responds to the Real and what it inscribes, tying it to the Symbolic and Imaginary, Lacan called the sinthoma. Several signs and clinical fragments weave the debate, including on Alzheimer's as well as the treatment of the Real by the real, sustained by other notions of old age.